2023
DOI: 10.1136/jitc-2022-005854
|View full text |Cite
|
Sign up to set email alerts
|

Changes in circulating tumor DNA and outcomes in solid tumors treated with immune checkpoint inhibitors: a systematic review

Abstract: BackgroundQuantification of circulating tumor DNA (ctDNA) levels is a reliable prognostic tool in several malignancies. Dynamic changes in ctDNA levels in response to treatment may also provide prognostic information. Here, we explore the value of changes in ctDNA levels in response to immune checkpoint inhibitors (ICIs).MethodsWe searched MEDLINE (host: PubMed) for trials of ICIs in advanced solid tumors in which outcomes were reported based on change in ctDNA levels. ctDNA reduction was defined as reported i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…It has been demonstrated that ctDNA clearance is associated with significantly better outcomes beyond 2 years after initiating ICIs 197 . Of note, early evidence did not seem to indicate a consistent association between ctDNA dynamic changes and TMB or PD‐L1 expression 194,198,199 . Compared with this, Kim et al 200 .…”
Section: Soluble Systemic Markers Of Immunotherapymentioning
confidence: 99%
“…It has been demonstrated that ctDNA clearance is associated with significantly better outcomes beyond 2 years after initiating ICIs 197 . Of note, early evidence did not seem to indicate a consistent association between ctDNA dynamic changes and TMB or PD‐L1 expression 194,198,199 . Compared with this, Kim et al 200 .…”
Section: Soluble Systemic Markers Of Immunotherapymentioning
confidence: 99%
“…Detecting circulating DNA offers multiple opportunities in (a) early cancer diagnosis (b) assessment of minimal residual disease (MRD) (c) disease tracking during anticancer treatment—“molecular response” to therapy and (d) uncovering tumour heterogeneity and novel targets conferring treatment resistance [ 57 , 58 , 59 , 60 , 61 , 62 ]. Variant allele frequency (VAF) is the most common readout for a mutation detected in ctDNA and is defined as the fraction of cfDNA molecules sequenced at a particular locus that harbours the variant of interest.…”
Section: Circulating Tumour Dna In Melanomamentioning
confidence: 99%
“…Molecular response and ctDNA kinetics refer to VAF dynamics during treatment, and it is worth mentioning that, besides tumour driver mutations, these can encompass the characterisation of neoantigens and/or chromosomal number aberrations [ 83 , 84 , 85 ]. Several studies and meta-analyses have attempted to highlight the robustness of ctDNA as a biomarker of treatment response, which can guide treatment duration or monitoring intensity in a pan-cancer fashion [ 59 , 62 , 68 , 86 , 87 , 88 ]. Across 16 tumour types, including melanoma, Zhang et al confirmed that mean VAF pre-treatment with immune checkpoint inhibition was prognostic of overall survival [OS; stratified by the median; unadjusted HR, 0.58; 95% confidence interval (CI), 0.49–0.69; p < 0.0001].…”
Section: Circulating Tumour Dna In Melanomamentioning
confidence: 99%
“…Thus, often tissue biopsy in operation theater is required to prove the diagnosis of HPV + OPSCC, causing additional invasive procedure, diagnostic delays and cost increase 18 . Despite cell free DNA (cfDNA) is a promising biomarker for diagnosis and monitoring of cancer treatment as well as for detection of residual disease and recurrences, 19–21 its use is limited by increasing challenges linked to sensitivity (detection of somatic cfDNA alterations against a normal DNA background) and specificity (cfDNA alterations are not intrinsically specific for a given type of cancer) 22,23 . On the contrary, circulating tumor HPV DNA (ctHPVDNA), released by HPV‐related cancers, is more easily identified than altered somatic cfDNA, and is able to indicate the possible localization of primary tumors, thus improving sensitivity and specificity, respectively 24–26 .…”
Section: Introductionmentioning
confidence: 99%